2014
DOI: 10.1016/j.celrep.2013.12.030
|View full text |Cite
|
Sign up to set email alerts
|

The Earliest Transcribed Zygotic Genes Are Short, Newly Evolved, and Different across Species

Abstract: The transition from maternal to zygotic control is fundamental to the life cycle of all multicellular organisms. It is widely believed that genomes are transcriptionally inactive from fertilization until zygotic genome activation (ZGA). Thus, the earliest genes expressed probably support the rapid cell divisions that precede morphogenesis and, if so, might be evolutionarily conserved. Here, we identify the earliest zygotic transcripts in the zebrafish, Danio rerio, through metabolic labeling and purification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
261
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(305 citation statements)
references
References 43 publications
38
261
4
2
Order By: Relevance
“…Transcription of these sites preceded the nucleus-wide transcription onset after mitosis (Figure 6 C). Previous work revealed that the miR-430 gene cluster is very highly transcribed in late blastula zebrafish embryos (Heyn et al, 2014). We detected primary miR-430 transcripts at the prominent transcription sites, suggesting a role for miR-430 transcription in their formation (SI Figure 11).…”
Section: Microenvironments Form By Rna Accumulation and Expel Not Tramentioning
confidence: 53%
See 1 more Smart Citation
“…Transcription of these sites preceded the nucleus-wide transcription onset after mitosis (Figure 6 C). Previous work revealed that the miR-430 gene cluster is very highly transcribed in late blastula zebrafish embryos (Heyn et al, 2014). We detected primary miR-430 transcripts at the prominent transcription sites, suggesting a role for miR-430 transcription in their formation (SI Figure 11).…”
Section: Microenvironments Form By Rna Accumulation and Expel Not Tramentioning
confidence: 53%
“…4 Rate of Pol II escape from promoter-paused state (Stasevich, Hayashi-Takanaka, et al, 2014). 5 Average time of 10 minutes for transcript completion estimated based on a typical length of genes transcribed at late blastula stage of 10 kb (Heyn et al, 2014) and a typical Pol II transcription rate of 1 kb/min (Wada et al, 2009;Jonkers, Kwak and Lis, 2014;Stasevich, Hayashi-Takanaka, et al, 2014). 6 Within the range of typical nuclear retention times of completed transcripts (Bahar Halpern et al, 2015;Battich, Stoeger and Pelkmans, 2015).…”
Section: Details Of the Physical Modelmentioning
confidence: 99%
“…4D). Recently, it was demonstrated that a small number of genes are transcribed prior to the zebrafish MBT, so we assessed the replication timing of those genes (Heyn et al 2014). The pre-MBT-expressed gene set was significantly earlier replicating than genes overall, consistent with a relationship between their transcription and early replication (Fig.…”
Section: A Pre-mbt Replication Timing Program Anticipates Initial Zygmentioning
confidence: 74%
“…(b) Many of the genes that were differentially regulated had a short predicted protein product (~100 amino acids long, Figure 4a, Supplementary Figure S3). Recent studies in eukaryotes have shown that short genes are transcribed and translated rapidly compared with longer genes, perhaps providing a mechanism for fast response to changes in conditions or during development (Shah et al, 2013;Heyn et al, 2014). Such genes also evolve rapidly and may be important in shaping genomic novelty and evolutionary plasticity (Grishkevich and Yanai, 2014;Heyn et al, 2014).…”
Section: Transcriptome Of Prochlorococcus In Co-culture D Aharonovichmentioning
confidence: 99%
“…Recent studies in eukaryotes have shown that short genes are transcribed and translated rapidly compared with longer genes, perhaps providing a mechanism for fast response to changes in conditions or during development (Shah et al, 2013;Heyn et al, 2014). Such genes also evolve rapidly and may be important in shaping genomic novelty and evolutionary plasticity (Grishkevich and Yanai, 2014;Heyn et al, 2014). Genes encoding for short proteins are common in Prochlorococcus (Figure 4c) yet, for the most part, their roles are still unknown (Zhaxybayeva et al, 2007;Whidden et al, 2014).…”
Section: Transcriptome Of Prochlorococcus In Co-culture D Aharonovichmentioning
confidence: 99%